Case report: Self-expanding transcatheter valve implantation (Acurate Neo 2) in a very small native aortic annulus - Medda, Massimo; Casilli, Francesco; Bande, Marta; Tespili, Maurizio; Donatelli, Francesco (Frontiers in Cardiovascular Medicine, 2023)
Symptomatic severe aortic stenosis (AS) in intermediate-to-high surgical risk patients is currently treated with transcatheter aortic valve replacement (TAVR). The presence of a small aortic annulus (SAA) has been associated with a higher incidence of prosthesis–patient mismatch (PPM) when surgical aortic valve replacement (sAVR) is performed (1). Multicenter registries have recently published the comparative data between different transcatheter heart valve (THV) in patients with SAA, documenting low clinical event rates, lower transvalvular gradients and less PPM (2-3). We present a case of a TAVR in a SAA; to our knowledge, this is among the smallest native aortic annulus so far described and treated percutaneously in a tricuspid stenotic aortic valve with a self-expanding (SE) THV Acurate Neo 2